Improved Mucoadhesive Properties of Repaglinide-Loaded Nanoparticles: Mathematical Modelling through Machine Learning-Based Approach - Nader Ibrahim Namazi (Indonesian Journal of Chemistry, 2023)
This research work aims to develop a modified repaglinide-loaded chitosan-ethyl cellulose nanoparticles (RPG-ECSNPs) as a novel sustained-release dosage form with improved mucoadhesive properties using an emulsification solvent-evaporation technique. The RPG-ECSNPs with different particle sizes were prepared from various polymers containing ethyl cellulose (EC) as the internal phase and chitosan (CS) as the external phase, and the use of surfactants, including Tween 80 and poloxamer 188 as emulsifiers. In vitro drug release, drug loading amount, and entrapment efficiency have been influenced by changes in the concentrations of CS and EC. The mean droplet size and zeta potential of RPG-ECSNPs were 213 ± 8.5 nm and 16.4 ± 2.4 mV, respectively. The optimized formulation's entrapment efficiency was 66 ± 2.3%, and drug loading was 7.9 ± 1.65%. The release profile was significantly higher in PBS (90%) than in diluted hydrochloric acid (30%) during 24 h of the study. The mucoadhesive function of the particles was examined in vitro using part of rat intestines. The highest adhesive % was observed for the chitosan-coated NPs. No adhesive properties were noticed for chitosan-free NPs (P-value > 0.05). This indicated that ECSNPs can be successfully utilized for sustained and controlled drug delivery of RPG through the GIT.